Harnessing Diesel-Degrading Potential of an Antarctic Microalga from Greenwich Island and Its Physiological Adaptation - Lim, Zheng Syuen; Wong, Chiew-Yen; Ahmad, Siti Aqlima; Puasa, Nurul Aini; Phang, Lai Yee; Shaharuddin, Noor Azmi; Merican, Faradina; Convey, Peter; Zulkharnain, Azham; Shaari, Hasrizal; Azmi, Alyza Azzura; Kok, Yih-Yih; et al. (My University, 2023)
Phytoremediation is a plant-based approach to extract, stabilise, eliminate, or render pollutants into less harmful form. The study highlights the use of a native polar microalga as a means of phytoremediation in Antarctica where imported microbes are prohibited. Since 1959, Antarctica has been a protected region to preserve its dynamic ecosystems, but it is increasingly vulnerable to climate change and pollution. One of the anthropogenic disturbances in the continent is diesel spillage. Due to the extreme polar environment, natural attenuation of spilled diesel is severely hindered; hence, the problem calls for an effective and sustainable solution. This laboratory study proved that Antarctic microalga was capable of removing diesel (57.6%) through biodegradation and biosorption in the span of nine days. Meanwhile, mixotrophic cultivation triggered the vacuolar activities and potentially stimulated lipid assimilation in the cells. The microalgal-based process offers a cheap alternative in water decontamination while bearing the economic potential through the secretion of valuable products, such as biolipids. Abstract: Microalgae are well known for their metal sorption capacities, but their potential in the remediation of hydrophobic organic compounds has received little attention in polar regions. We evaluated in the laboratory the ability of an Antarctic microalga to remediate diesel hydrocarbons and also investigated physiological changes consequent upon diesel exposure. Using a polyphasic taxonomic approach, the microalgal isolate, WCY_AQ5_1, originally sampled from Greenwich Island (South Shetland Islands, maritime Antarctica) was identified as Tritostichococcus sp. (OQ225631), a recently erected lineage within the redefined Stichococcus clade. Over a nine-day experimental incubation, 57.6% of diesel (similar to 3.47 g/L) was removed via biosorption and biodegradation, demonstrating the strain's potential for phytoremediation. Fourier transform infrared spectroscopy confirmed the adsorption of oil in accordance with its hydrophobic characteristics. Overall, degradation predominated over sorption of diesel. Chromatographic analysis confirmed that the strain efficiently metabolised medium-chain length n-alkanes (C-7 to C-21), particularly n-heneicosane. Mixotrophic cultivation using diesel as the organic carbon source under a constant light regime altered the car/chl-a ratio and triggered vacuolar activities. A small number of intracellular lipid droplets were observed on the seventh day of cultivation in transmission electron microscopic imaging. This is the first confirmation of diesel remediation ability in an Antarctic green microalga.
Keywords: antarctic microalga; phytoremediation; diesel biodegradation; biosorption; hydrocarbon